Enhancing Enviromental Preservation Through Mangrove Afforestation In The Youtefa Bay Area - Tita Deitiana; Nila Pusvikasari (International Journal Of Community Service, 2025)
The degradation of mangrove areas is often caused by human activities such as timber exploitation, conversion of mangrove areas into roads, bridges, and residential settlements, as well as natural environmental changes. Youtefa Bay Nature Tourism Park is a conservation area characterized by stunning natural landscapes, extensive coastlines, mangrove forests, lowland tropical forests, and a rich marine ecosystem. if managed properly, the area holds great potential to generate substantial benefits for the surrounding communities. However, the current reality on the ground reveals that the management of the area remains fragmented and poorly planned. This uncoordinated approach has contributed to various environmental problems within the conservation area. Mangrove forests are among the most strategic coastal ecosystems. In Indonesia, the total area of mangrove forests continues to decline annually, primarily due to land-use changes for housing and the development of various infrastructure projects. This community engagement activity aimed to contribute to the conservation of mangrove forests in Youtefa Bay Nature Tourism Park. The initiative was carried out on October 18-19th 2023, by the Forum Manjemen Indonesia (FMI). The planting method used was the single planting technique. The mangrove planting event was successfully conducted and received appreciation from various stakeholders, particularly government representatives and lecturers from the Forum Manajemen Indonesia. To maximize the ecological function of this conservation area, it is crucial to ensure the ongoing preservation of its mangrove forests. One concrete effort undertaken is the reforestation of mangrove areas through collaborative action. this community services were part of a series of program organized by FMI in Papua and was designed to support mangrove ecosystem rehabilitation while enhancing the roles of local communities, academic institutions, and government bodies in environmental conservation.